A prospective, real-world, multinational study of naloxegol for patients with cancer pain diagnosed with opioid-induced constipation - the NACASY Study - Davies, Andrew (My University, 2022)
The Naloxegol Cancer Study (NACASY) was a multinational European study aimed to evaluate the 4-week safety and efficacy of naloxegol in a real-world setting in patients with cancer pain diagnosed with opioid-induced constipation. The primary safety endpoint was the incidence of adverse events leading to study discontinuation. We recruited 170 patients who received at least one dose of naloxegol (i.e., safety population). Out of 170 patients, 20 (11.8%, 95%CI 6.9-16.6) discontinued the study due to adverse events, and, of them, 12 (7.1%, 95%CI 3.2-10.9%) were study discontinuations due to naloxegol-related adverse events. From 76 patients subjects who had completed both 4 weeks of treatment and 28 days of the diary, 55 patients (72.4%, 95% CI 62.3-82.4%) were regarded as responders (i.e., showed ≥3 bowel-movements per week and an increase of ≥1 bowel-movement over baseline) to naloxegol treatment. The Patient Assessment of Constipation-Quality of Life Questionnaire total score and all its subscales improved from baseline to 4 weeks of follow up. Our findings support and provide new evidence about the beneficial effect of naloxegol in terms of improvement of constipation and quality-of-life in patients with cancer-related pain and opioid-induced constipation and show a safety profile consistent with previous pivotal and real-world studies. Keywords: MOVANTIK; PAMORA; cancer pain; naloxegol; opioid-induced constipation; real-world The Naloxegol Cancer Study (NACASY) was a multinational European study aimed to evaluate the 4-week safety and efficacy of naloxegol in a real-world setting in patients with cancer pain diagnosed with opioid-induced constipation. The primary safety endpoint was the incidence of adverse events leading to study discontinuation. We recruited 170 patients who received at least one dose of naloxegol (i.e., safety population). Out of 170 patients, 20 (11.8%, 95%CI 6.9-16.6) discontinued the study due to adverse events, and, of them, 12 (7.1%, 95%CI 3.2-10.9%) were study discontinuations due to naloxegol-related adverse events. From 76 patients subjects who had completed both 4 weeks of treatment and 28 days of the diary, 55 patients (72.4%, 95% CI 62.3-82.4%) were regarded as responders (i.e., showed ≥3 bowel-movements per week and an increase of ≥1 bowel-movement over baseline) to naloxegol treatment. The Patient Assessment of Constipation-Quality of Life Questionnaire total score and all its subscales improved from baseline to 4 weeks of follow up. Our findings support and provide new evidence about the beneficial effect of naloxegol in terms of improvement of constipation and quality-of-life in patients with cancer-related pain and opioid-induced constipation and show a safety profile consistent with previous pivotal and real-world studies.
PUBLISHED
Keywords: MOVANTIK; PAMORA; Cancer pain; Naloxegol; Opioid-induced constipation; Real-world; Cancer